Bringing Safe and Standardized Cell Therapies to Industrialized Processing for Burns and Wounds - Laurent, Alexis; Lin, Poyin; Scaletta, Corinne; Hirt-Burri, Nathalie; Michetti, Murielle; de Buys Roessingh, Anthony S.; Raffoul, Wassim; She, Bin-Ru; Applegate, Lee Ann (Frontiers in Bioengineering and Biotechnology, 2020)
Cultured primary progenitor cell types are worthy therapeutic candidates for regenerative medicine. Clinical translation, industrial transposition and commercial implementation of products based on such cell sources are mainly hindered by economic and technical barriers, as well as stringent regulatory requirements. Applied research in allogenic cellular therapies in the Lausanne University Hospital (CHUV) focuses on cell source selection technique optimization. The use of fetal progenitor cell sources in Switzerland is regulated through a Federal Transplantation Program and an associated Fetal Biobank. Clinical applications of cultured primary progenitor dermal fibroblasts have been optimized in the CHUV since the 1990s. These novel cell sources have been developed for use in “Progenitor Biological Bandages” for pediatric burn patients and adults presenting chronic wounds. A single organ donation procured in 2009 enabled the establishment of a standardized cell source for clinical and industrial developments to date. Non-enzymatically isolated primary dermal progenitor fibroblasts (FE002-SK2 cell type) served for the establishment of a clinical-grade Parental Cell Bank, based on a patented method. Optimized bioprocessing methodology for the FE002-SK2 cell type has demonstrated that extensive and consistent progenitor cell banks can be established. Most importantly, highly successful industrial transposition and up-scaling of biobanking enabled the establishment of tiered Master and Working Cell Banks using Good Manufacturing Practices. Successive and successful transfers of technology, know-how and materials to different countries around the world have been performed. Extensive developments based on the FE002-SK2 cell source have led to clinical trials for burns and wound dressing. Said trials were approved in Japan, Taiwan, USA and are continuing in Switzerland. The Swiss Fetal Transplantation Program and pioneer clinical experience in the CHUV Burn Center over three decades constitute concrete indicators that primary progenitor dermal fibroblasts should be considered as therapeutic flagships in the domain of wound healing and for regenerative medicine in general. Indeed, one single organ donation potentially enables millions of patients to benefit from high-quality, safe and effective regenerative therapies. This work presents a technical and translational overview of the described progenitor cell technology harnessed in Switzerland as a cellular therapy for treatment of burns and wounds around the globe.